2019
DOI: 10.1021/acs.jpcc.9b03647
|View full text |Cite
|
Sign up to set email alerts
|

Red-Shifted Photoluminescence from Crystal Edges Due to Carrier Redistribution and Reabsorption in Lead Triiodide Perovskites

Abstract: Photoluminescence (PL) of CH3NH3PbI3 perovskites depends strongly on sample preparation, atmosphere, crystal size, and so forth. However, the origin of these dependencies is always misunderstood because of the co-works of many different factors. Herein, we prepared hexagonal-shaped single crystals with tens of micrometers in size and observed a red-shifted PL emission (800–830 nm) mainly from the crystal edges besides the usual band-to-band transition (760 nm) from the central regions. Also, significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
(62 reference statements)
0
28
0
Order By: Relevance
“…In general, it has been shown that self‐absorption effects can play an important role and need to be considered when analyzing measured PL spectra. [ 16–22 ] We recently demonstrated that self‐absorption can even lead to additional peaks in measured PL. With a relatively simple optical model it was possible to reproduce and analyze the additional peaks in the case of pure tetragonal or orthorhombic crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been shown that self‐absorption effects can play an important role and need to be considered when analyzing measured PL spectra. [ 16–22 ] We recently demonstrated that self‐absorption can even lead to additional peaks in measured PL. With a relatively simple optical model it was possible to reproduce and analyze the additional peaks in the case of pure tetragonal or orthorhombic crystal phases.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of a different crystal phase, an atmosphere effect and a degradation of the sample, reabsorption effects, radiative recombination involving shallow trapping levels and luminescence from the crystal edges [28] could all be possible reasons for the red shift. We attributed this red shift to the relative change between the intensities of the two lowest energy peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The distance between the second and third peaks is 62 and 7 meV for samples S1 and S2, respectively. A possible reason of this separation can be attributed to the presence of another phase of perovskite [42][43][44], different grain sizes [45] and emissions from the interior or boundaries of the grains [28,45,46]. However, the addition of small amounts of cesium (Cs) in a triple cation (Cs/MA/FA) configuration resulted in the formation of monolithic grains of a purer perovskite [47] and in the suppression of possible phase transitions [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, such a specific method of optical pumping, based on the tail of the TE 4 mode traveling along the PMMA cladding layer, provides a quasiuniform excitation of the MAPI layer over the whole length of the waveguide (mm scale). Moreover, since the whole MAPI film is excited, the PL reabsorption effect, which is a well-known issue in MHP layers [39,40], is minimized with this scheme, even below the ASE threshold. Indeed, a study of ASE in waveguides of different lengths reveals that the reabsorption-induced redshift of the PL line is only 10 meV (5 nm) for the longest (3 mm) waveguides, as observed in Fig.…”
Section: B Design Of Optical Waveguidesmentioning
confidence: 99%